1998
DOI: 10.1056/nejm199812103392401
|View full text |Cite|
|
Sign up to set email alerts
|

Unruptured Intracranial Aneurysms — Risk of Rupture and Risks of Surgical Intervention

Abstract: The likelihood of rupture of unruptured intracranial aneurysms that were less than 10 mm in diameter was exceedingly low among patients in group 1 and was substantially higher among those in group 2. The risk of morbidity and mortality related to surgery greatly exceeded the 7.5-year risk of rupture among patients in group 1 with unruptured intracranial aneurysms smaller than 10 mm in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
216
0
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,648 publications
(258 citation statements)
references
References 17 publications
10
216
0
16
Order By: Relevance
“…Sedivy et al [11] previously demonstrated that human cells have fractal dimensions in dysplastic and control nuclei derived from uterus cervix cone biopsies. Thus, our findings are consistent with previous reports [11, 15]. It is worth pointing out that there was a correlation between the fractal dimension and the aggressiveness of the lymphoma, i.e.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Sedivy et al [11] previously demonstrated that human cells have fractal dimensions in dysplastic and control nuclei derived from uterus cervix cone biopsies. Thus, our findings are consistent with previous reports [11, 15]. It is worth pointing out that there was a correlation between the fractal dimension and the aggressiveness of the lymphoma, i.e.…”
Section: Discussionsupporting
confidence: 94%
“…In a related study, Adam et al [15] calculated the fractal dimension of nuclear chromatin (using the Minkowski-Bouligand method extended to three dimensions) of blasts derived from 28 patients with acute B lymphoblastic leukemia and assessed its prognostic importance. While fractal dimension had no prognostic importance in that study, goodness of fit of the fractal dimension, estimated by R 2 , correlated with prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment can be done by neurosurgical clipping and by coil embolisation. In systematic reviews of published series, surgical treatment was associated with a permanent morbidity of 11% and a mortality of 3% [6, 7], and coil embolisation with a rate of permanent procedural complications of 7% [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Показа-но, что разорвавшиеся аневризмы имеют большие размеры по сравнению с неразорвавшимися [28,59]. При этом единых представлений о критическом размере нет.…”
Section: морфологические параметры и локализацияunclassified
“…При этом единых представлений о критическом размере нет. По одним данным, повышенный риск разрыва имеют аневризмы более 10 мм в диаметре [28,59,60], по другим -большинство САК проис-ходят из аневризм менее 10 мм [61][62][63] …”
Section: морфологические параметры и локализацияunclassified